Hydroecological assessment of the Kazakh part of the Yertis River under conditions of industrial development - Valentina Kolpakova; Yuliya Yeremeyeva; Samal Anapyanova; Gulnaz Mamyrbekova; Roza Nurekenova; Laura Utepbergenova; Zhanbolat Shakhmov; Aleksej Aniskin (Results in Engineering)
This article analyzes the impact of climate in the conditions of industrial development on the flow and ecological condition of the Kazakhstan part of the river Yertis on the territory of East Kazakhstan (EKR), Abay and Pavlodar regions. The research is based on the analysis of data from the meteorological base of the Republican State Enterprise (RSE) «Kazhydromet» for the period from 2019 to 2023. The relationship between air temperature, precipitation and the flow of the river Yertis is shown. The results of the analysis showed that for the last 5 years there is a decrease in the flow of the river Yertis from China and the flow inflow to the territory of Russia. The water quality of the Irtysh River was assessed in the context of administrative regions. Water quality was assessed by 18 hydrochemical indicators in 14 sites on the border with the People's Republic of China in the area of Boran village; above and below major cities - Ust-Kamenogorsk, Semey and Pavlodar; Priirtyshskoye village on the border with the Russian Federation. The results of the assessment of the environmental condition of the Yertis River showed that the most polluted is the section of the river on the territory of East-Kazakhstan region.